The crossbreeding program of beef and milk production at the National Animal Husbandry Research Station, Naivasha - Were, H.R.; Meyn, K.; Wilkins, J.V. (1969)
Report of the livestock improvement programme at Naivasha, Kenya. Discussions and data on milk yield, mothering ability, growth rate and carcass characteristics of Sahiwal cattle and Boran cattle crosses; and comparison of their crossbreeds with Friesian cattle under calf rearing systems of hand feeding and suckling included.